2020
DOI: 10.29408/jel.v6i2.2012
|View full text |Cite
|
Sign up to set email alerts
|

Kemampuan Mengkonstruksi Bukti Geometri Mahasiswa Calon Guru Matematika Pada Perkuliahan Geometri

Abstract: This study aims to analyze and describe the ability to construct proofs of perspective teacher mathematics students in basic geometrical lectures on the concepts of alignment, triangles, and concordance of two triangles. This research uses a descriptive qualitative method involving 35 prospective mathematics students at the Universitas PGRI Semarang. This study uses a qualitative descriptive method involving 35 students. The results of this study show that: (1) 28% of students sketched diagrams and used geomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…K2 writes down known things based on the pictures created. This step is in line with (Maarif et al, 2020) that the first step in the proof is to create an image based on the information in the question.…”
Section: Building Idea Stagementioning
confidence: 64%
See 3 more Smart Citations
“…K2 writes down known things based on the pictures created. This step is in line with (Maarif et al, 2020) that the first step in the proof is to create an image based on the information in the question.…”
Section: Building Idea Stagementioning
confidence: 64%
“…Test result data is disclosed and used to investigate student decision-making. The basis for grouping student answers was adapted from (Arnawa et al, 2007;Maarif et al, 2020;Masters, 2010;Middleton, 2009) and is presented in Table 1. Less than half of the evidence is correct.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research shows low results in understanding geometry, as revealed by Sunardi & Yudianto (2016), where 61 out of 82 students scored below 60 in geometry material. Students also experience difficulties constructing proofs in geometry, as (Maarif et al, 2020) stated. Focusing on quadrilaterals as an example, theorems such as Varignon's theorem, "If the midpoints of each side of a quadrilateral are connected, a parallelogram is formed," is one of the theorems that require proof (Grigorieva, 2013).…”
Section: A Introductionmentioning
confidence: 99%